Metabolic power and energy expenditure in an international men`s hockey tournament - Polglaze, T.; Dawson, B.; Buttfield, A.; Peeling, P. (Journal of Sports Sciences, 2018)
The purpose of this study was to ascertain the typical metabolic power characteristics of elite men`s hockey, and whether changes occur within matches and throughout an international tournament. National team players (n = 16), divided into 3 positional groups (strikers, midfielders, defenders), wore Global Positioning System devices in 6 matches. Energetic (metabolic power, energy expenditure) and displacement (distance, speed, acceleration) variables were determined, and intensity was classified utilising speed, acceleration and metabolic power thresholds. Midfielder`s average metabolic power (11.8 ± 1.0 W/kg) was similar to strikers (11.1 ± 1.3 W · kg-1) and higher than defenders (10.8 ± 1.2 W/kg, P = 0.001). Strikers (29.71 ± 3.39 kJ/kg) expended less energy than midfielders (32.18 ± 2.67 kJ/kg, P = 0.014) and defenders (33.23 ± 3.96 kJ/kg, P < 0.001). Energetic variables did not change between halves or across matches. Across all positions, over 45% of energy expenditure was at high intensity (>20 W/kg). International hockey matches are intense and highly intermittent; however, intensity is maintained throughout matches and over a tournament. In isolation, displacement measures underestimate the amount of high-intensity activity, whereas the integration of instantaneous speed and acceleration provides a more comprehensive assessment of the demands for variable-speed activity typically occurring in hockey matches.